Study on agricultural cropping pattern change in a water stress area of North-west region of Bangladesh a case study in Sapahar Upazilla under Naogaon district - Miah, Md. Ruhul Amin (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development, 2022.